2018
DOI: 10.5590/jswgc.2018.03.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Victimization of the Homeless: Public Perceptions, Public Policies, and Implications for Social Work Practice

Abstract: Homeless individuals are particularly vulnerable to victimization, sometimes resulting in fatalities. Theories of victimization prove useful to understanding the risks inherent in being homeless as well as the public’s perception of the homeless population. Problematically, public policy that criminalizes this population may exacerbate the victimization of this group. Municipalities have turned to law enforcement and the criminal justice system to respond to people living in public spaces. Programs that ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The greater vulnerability of WEH is acknowledged and expressed in the most recognized definitions of homelessness, which include specific categories for WEH and acknowledge that WEH are especially vulnerable when they are literally homeless (e.g., rough sleepers) (Busch-Geertsema et al, 2016; European Federation on National Organizations Working with the Homeless [FEANTSA], 2005; Turner et al, 2018). WEH experiencing literal street homelessness are the most at-risk population among IEH (Nyamathi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The greater vulnerability of WEH is acknowledged and expressed in the most recognized definitions of homelessness, which include specific categories for WEH and acknowledge that WEH are especially vulnerable when they are literally homeless (e.g., rough sleepers) (Busch-Geertsema et al, 2016; European Federation on National Organizations Working with the Homeless [FEANTSA], 2005; Turner et al, 2018). WEH experiencing literal street homelessness are the most at-risk population among IEH (Nyamathi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In Hungary in 2010 an anti-homeless campaign banned people from begging and picking up left over food from bins (Faragó et al, 2021). These anti-homeless laws have reinforced the negative perceptions of PEH among the public and authorities and lead to support for punitive policies (Turner et al, 2018).…”
Section: Challenges In Addressing Homelessness In Mexico Citymentioning
confidence: 99%
“…A landmark study by Olufemi [39] found that unhoused people are often referred to using derogatory and exclusionary language which is associated with the perception that unhoused people are out-group. In addition, past research has found that unhoused people are perceived to have social stigmas such as a criminal history or poor work ethic [40][41][42]. This is a misconception, as unhoused people typically are involved in society and their community.…”
Section: Houselessnessmentioning
confidence: 99%